Cinematic Borderlands: Jean Vigo's L'Atalante and the Allure of entre-deux. Issue 3 (27th May 2017) - Hunt, Brian
ABSTRACT: Offering new insight into Jean Vigo's masterpiece L'Atalante through the lens of spatial theory, this article claims that Vigo situated the majority of the film's action on a borderland in order to allude to the productive possibilities of surrealism and montage. Geographical borders are mediating bodies which, for Michel de Certeau, also represent a "parole de la limite" [ the language of limits ] that concomitantly establishes communication and separation between two sides. The discursive mobility created by the border is equally and intricately linked to spatial mobility, since, as Certeau continues, the border is also "un passage." Instead of passing through or across a border, the protagonists of Vigo's film opt to pass along, and thus inhabit the border. Drawing on Certeau's observations on borders as productive zones, this article demonstrates a clear link between the canal-as-border and the surrealist aesthetic, while opening up a discussion of montage as an invisible, yet essential border in cinema.